Control and Management of Distribution System Using MAS - Mahdi Mozaffari Legha (Journal of Global Pharma Technology, 2017)
In this paper, application of MAS for the frequency & Voltage control of islanded Micro grid by Load shedding method is presented. Frequency & Voltage stability of micro grids under islanded operation attracts particular attention recently. The islanded micro grid makes its frequence & Voltage control more difficult than the conventional grids. On This strategy, agents sent data and furthermore each component has its own to center operating decisions (MGCC). The simulation results show the promising performance of the proposed structure of the controller based on multi agent systems. Keywords: Control and Management, Distribution System.